If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + -7x = 2x + 15 Reorder the terms: 67 + -7x = 15 + 2x Solving 67 + -7x = 15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 67 + -7x + -2x = 15 + 2x + -2x Combine like terms: -7x + -2x = -9x 67 + -9x = 15 + 2x + -2x Combine like terms: 2x + -2x = 0 67 + -9x = 15 + 0 67 + -9x = 15 Add '-67' to each side of the equation. 67 + -67 + -9x = 15 + -67 Combine like terms: 67 + -67 = 0 0 + -9x = 15 + -67 -9x = 15 + -67 Combine like terms: 15 + -67 = -52 -9x = -52 Divide each side by '-9'. x = 5.777777778 Simplifying x = 5.777777778
| 10d+3e-5d-e= | | 11x=90-1x | | -5x+3=13 | | x+3x=5 | | e^2x=1 | | 7x-4=3x+23 | | 6a+86=13a-5 | | y=x^2+10+12 | | 36-2x=7x+21 | | e^0.01t=e^0.02t-1/5 | | 7-10x=59-38x | | 6(x-1)=3 | | 5(t-2)=3(t-2) | | 82-5x=13x+24 | | 5(x+3)=3(x+7) | | t-22=-45 | | -11-5x=9-x | | -22-23= | | 100-7x=11x+24 | | X+3y=82 | | 2(t+1)=3(t+2) | | 3x+13y=-9 | | 10n+14=124 | | 4(p+2)=5(p-3) | | 3x/4+7x/2=20 | | 10x+14=142 | | 70-11x=17x+14 | | 2(a+2)=3(a+1) | | b+(b-63)=637 | | 4x^2-15x+19=-2x+9 | | 11x+7=63-4x | | 5p=6(p-1) |